Electrode for secondary battery, and secondary battery
By optimizing the active material layer in secondary battery electrodes through controlled Voronoi analysis, the electrode achieves uniform material dispersibility and reduced ion diffusion resistance, leading to higher operating voltage at high current densities.
Patent Information
- Application Number
- JP2023144534
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-06
- Publication Date
- 2025-03-18
AI Technical Summary
Existing secondary battery electrodes face challenges in achieving high operating voltage at high current densities due to insufficient material dispersibility in the active material layer, leading to increased diffusion resistance of ions.
The electrode design incorporates an active material layer with a conductive aid, where the average area and standard deviation of the Voronoi region obtained by Voronoi analysis are within specific ranges, ensuring uniform dispersibility of materials and reduced ion diffusion resistance.
This approach results in a secondary battery with improved electrical conductivity and reduced ion diffusion resistance, enabling higher operating voltage at high current densities and enhanced energy efficiency.
Smart Images

Figure 2025037543000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrode for a secondary battery and a secondary battery. [Background technology]
[0002] In recent years, research and development into secondary batteries that contribute to energy efficiency has been conducted to ensure that more people have access to affordable, reliable, sustainable, and advanced energy. The electrodes of secondary batteries generally have a current collector and an active material layer that can absorb and release ions (charge carriers) such as lithium ions. A coating method is known as a method for producing an active material layer. The coating method is a method in which a slurry for forming an active material layer, in which constituent materials such as an active material, a conductive assistant, and optionally a solid electrolyte, a binder, and a dispersant are dispersed in a solvent, is applied onto a current collector and then dried.
[0003] In order to improve the properties of the active material layer produced by the coating method, the materials and compositions of the slurry for forming the active material layer have been studied. For example, in order to achieve good dispersibility of the active material and solid electrolyte in the slurry for forming the active material layer while sufficiently increasing the binding force of the active material layer to the current collector, the use of two or more types of solvents has been studied (Patent Document 1). In order to suppress the aggregation of the conductive assistant in the slurry for forming the active material layer and improve the dispersibility of the conductive assistant, the use of a specific binder has been studied (Patent Document 2). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2015-82362 A [Patent Document 2] JP 2015-50017 A Summary of the Invention [Problem to be solved by the invention]
[0005] By the way, in the technology related to secondary batteries, one of the problems is to increase the potential of the operating voltage at high current density. In order to increase the potential of the operating voltage at high current density, it is effective to reduce the ion diffusion resistance of the active material layer of the electrode to facilitate the diffusion of ions in the active material layer. As a means for reducing the ion diffusion resistance of the active material layer, it is considered that one of the effective means is to uniformly disperse materials such as the active material and conductive assistant in the active material layer. However, according to the study by the present inventor, the dispersibility of materials in the conventional active material layer may be insufficient, and the operating voltage at high current density may be significantly reduced.
[0006] The present invention has been made in view of the above problems, and aims to provide an electrode for a secondary battery having an active material layer in which materials such as an active material and a conductive assistant are uniformly dispersed and which has low ion diffusion resistance, and a secondary battery having a high operating voltage at a high current density, which will ultimately contribute to energy efficiency. [Means for solving the problem]
[0007] The present inventors have found that the dispersibility (uniformity) of the active material layer can be appropriately grasped by using the area of the Voronoi region obtained by performing Voronoi analysis on an image of the cross section of the active material layer with the conductive assistant as the generating point and the standard deviation of the area of the Voronoi region. The inventors have confirmed that an electrode having an active material layer in which the average area of the Voronoi region and the average standard deviation of the area of the Voronoi region are at a predetermined value has a reduced diffusion resistance, and that a secondary battery using this electrode has a high operating voltage at a high current density, thereby completing the present invention. Thus, the present invention provides the following.
[0008] (1) A current collector and an active material layer disposed on at least one surface of the current collector, the active material layer including an active material and a conductive additive, and a cross-sectional image of the current collector is subjected to Voronoi analysis with the conductive additive as a generating point, and the average area of the Voronoi region obtained is 1.00 μm 2 More than 2.50μm 2An electrode for a secondary battery, wherein the standard deviation of the area of the Voronoi region is 0.20 or less and is within the following range.
[0009] In the secondary battery electrode of (1), the average value and standard deviation of the area of the Voronoi region obtained by performing Voronoi analysis with the conductive additive as the generating point are within the above ranges, and the conductive additive is uniformly dispersed in the active material layer, so that the electrical conductivity of the active material layer becomes uniform, which makes it easier for ions to diffuse throughout the active material layer and reduces the ion diffusion resistance of the active material layer.
[0010] (2) The electrode for a secondary battery according to (1), wherein the coefficient of variation of the area of the Voronoi region is 10.0% or less.
[0011] According to the secondary battery electrode of (2), since the coefficient of variation of the area of the Voronoi region is within the above range, the diffusion resistance of ions in the active material layer is further reduced.
[0012] (3) The electrode for a secondary battery described in (1) or (2), wherein the conductive assistant is spherical, and the ratio of the average particle size of the conductive assistant measured by a laser diffraction method to the average particle size of the active material measured by a laser diffraction method is within the range of 0.010 or more and 0.080 or less.
[0013] (3) According to the secondary battery electrode, the conductive additive is spherical and finer than the active material, so that the conductive additive can be easily dispersed uniformly in the active material layer, thereby further reducing the ion diffusion resistance in the active material layer.
[0014] (4) The electrode for a secondary battery according to any one of (1) to (3), further comprising a solid electrolyte, wherein a ratio of an average particle size of the solid electrolyte measured by a laser diffraction method to an average particle size of the active material measured by a laser diffraction method is within a range of 0.10 or more and 0.90 or less.
[0015] According to the secondary battery electrode of (4), since it contains a fine solid electrolyte compared to the active material, the ion diffusion resistance of the active material layer is further reduced, and therefore the secondary battery electrode of (4) is useful as an electrode for a solid-state battery.
[0016] (5) The electrode for a secondary battery according to any one of (1) to (4), wherein the active material has an average particle size measured by a laser diffraction method in the range of 1.0 μm or more and 5.0 μm or less.
[0017] According to the secondary battery electrode of (5), the active material has a fine average particle size within the above range and a large surface area, so that the ion diffusion resistance of the active material layer is further reduced.
[0018] (6) The electrode for a secondary battery according to any one of (1) to (5), which is for use as a positive electrode of a secondary battery.
[0019] The secondary battery electrode (6) is useful as a positive electrode for solid-state batteries and non-aqueous solvent secondary batteries.
[0020] (7) A secondary battery comprising the electrode for a secondary battery according to any one of (1) to (6).
[0021] According to the secondary battery of (7), since the secondary battery electrode is provided as described above, the reduction in operating voltage at high current density is small, and the operating voltage at high current density is high. Effect of the Invention
[0022] According to the present invention, it is possible to provide an electrode for a secondary battery having an active material layer in which materials such as an active material and a conductive assistant are uniformly dispersed and which has low ion diffusion resistance, and a secondary battery having a high operating voltage at high current density. [Brief description of the drawings]
[0023] [Figure 1] 1 is a cross-sectional view showing a secondary battery according to one embodiment of the present invention. [Diagram 2]FIG. 2 is a schematic diagram showing an example of a Voronoi diagram obtained by performing Voronoi analysis on a cross section of a positive electrode active material layer of a secondary battery according to one embodiment of the present invention, with a conductive assistant as a generating point. [Figure 3A] 2 is a secondary electron image of a cross section of a positive electrode active material layer obtained in Example 1. [Figure 3B] FIG. 2 is a Voronoi diagram in which the conductive assistant of the cross section of the positive electrode active material obtained in Example 1 is used as the generating point. [Figure 4A] 4 shows a frequency distribution of the average areas of Voronoi regions measured at 30 points on a cross section of a positive electrode active material layer obtained in Example 1. [Figure 4B] 1 shows a frequency distribution of the average areas of Voronoi regions measured at 30 points on a cross section of a positive electrode active material layer obtained in Example 2. [Figure 4C] 1 shows a frequency distribution of the average areas of Voronoi regions measured at 30 points on a cross section of a positive electrode active material layer obtained in Example 3. [Figure 4D] 13 is a frequency distribution of the average areas of Voronoi regions measured at 30 points on a cross section of a positive electrode active material layer obtained in Example 4. [Figure 4E] 1 shows a frequency distribution of the average areas of Voronoi regions measured at 30 points on a cross section of a positive electrode active material layer obtained in Comparative Example 1. [Figure 4F] 1 shows a frequency distribution of the average areas of Voronoi regions measured at 30 points on a cross section of a positive electrode active material layer obtained in Comparative Example 2. [Figure 4G] 13 is a frequency distribution of the average areas of Voronoi regions measured at 30 points on a cross section of a positive electrode active material layer obtained in Comparative Example 3. [Diagram 5] 4 is a graph showing IV characteristics of solid-state batteries fabricated using the positive electrodes obtained in Examples 1 to 4 and Comparative Examples 1 to 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] Hereinafter, a secondary battery electrode according to one embodiment of the present invention and a secondary battery using this electrode will be described in detail with reference to the drawings, but the present invention is not limited thereto.
[0025] Fig. 1 is a cross-sectional view showing a secondary battery according to one embodiment of the present invention. Fig. 2 is a schematic diagram showing an example of a Voronoi diagram obtained by performing Voronoi analysis on a cross section of a positive electrode active material layer of a secondary battery according to one embodiment of the present invention, with a conductive assistant as a generating point.
[0026] As shown in FIG. 1, the secondary battery 1 of this embodiment is a solid-state battery including an electrode laminate 10 and an exterior body 50 that houses the electrode laminate 10. The electrode laminate 10 is a laminate in which a positive electrode 20 and a negative electrode 30 are laminated with a solid electrolyte layer 40 interposed therebetween. The positive electrode 20 includes a positive electrode collector 21 and a positive electrode active material layer 22 arranged on the surface of the positive electrode collector 21 facing the solid electrolyte layer 40. The positive electrode collector 21 is connected to a positive electrode terminal 24 via a positive electrode lead wire 23. The negative electrode 30 includes a negative electrode collector 31 and a negative electrode active material layer 32 arranged on the surface of the negative electrode collector 31 facing the solid electrolyte layer 40. The negative electrode collector 31 is connected to a negative electrode terminal 34 via a negative electrode lead wire 33. A portion of the positive electrode terminal 24 and the negative electrode terminal 34 are exposed from the exterior body 50.
[0027] There are no particular limitations on the material or shape of the positive electrode current collector 21 as long as it has the function of collecting current from the positive electrode 20. Examples of materials for the positive electrode current collector 21 include aluminum, aluminum alloys, stainless steel, nickel, iron, and titanium, and among these, aluminum, aluminum alloys, and stainless steel are preferred. Examples of the shape of the positive electrode current collector 21 include a foil shape, a plate shape, and the like.
[0028] As shown in FIG. 2, in the positive electrode active material layer 22, in a Voronoi diagram obtained by performing Voronoi analysis with the conductive assistant 221 as the generating point, the average value of the area of the Voronoi region 222 is 1.00 μm 2 More than 2.50μm 2The average area of the voronoi regions 222 is an index of the distance between the conductive assistants 221. The standard deviation of the area of the voronoi regions 222 is an index of the variation in the distance between the conductive assistants 221. Therefore, when the average area and standard deviation of the voronoi regions 222 are within the above ranges, the conductive assistant 221 is uniformly dispersed in the positive electrode active material layer 22. The average area of the voronoi regions 222 is 1.50 μm 2 More than 2.00μm 2 The standard deviation of the area of the Voronoi region 222 may be within the range of 0.05 to 0.20. The coefficient of variation of the area of the Voronoi region 222 may be 10.0% or less, or may be within the range of 1.0% to 9.0%.
[0029] The Voronoi diagram can be obtained, for example, as follows. An electron reflection image is obtained for a cross section of the positive electrode active material layer 22 using a scanning electron microscope (SEM). The obtained electron reflection image is binarized into regions of the conductive assistant that do not reflect electrons and other regions that reflect electrons. A Voronoi analysis is performed using the conductive assistant regions of the obtained binarized image as generating points to obtain a Voronoi diagram.
[0030] The positive electrode active material layer 22 contains at least one type of positive electrode active material and a conductive assistant. The positive electrode active material is not particularly limited, and for example, a layered active material containing lithium, a spinel type active material, an olivine type active material, etc. can be used. Specific examples of the positive electrode active material include lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), LiNi p Mn q Co r O2(p+q+r=1), LiNipAlqCorO2(p+q+r=1), Lithium manganate (LiMn2O4), Li 1+x Mn 2-x-yExamples of such materials include Li-Mn spinel substituted with different elements represented by MO4 (x+y=2, M=at least one selected from Al, Mg, Co, Fe, Ni, and Zn), lithium titanate (oxide containing Li and Ti), and lithium metal phosphate (LiMPO4, M=at least one selected from Fe, Mn, Co, and Ni).
[0031] The shape of the positive electrode active material may be, for example, spherical, polyhedral, or amorphous. The spherical shape does not have to be a perfect sphere, and it is sufficient that the aspect ratio is 2 or less. The positive electrode active material may have an average particle size (D50) in the range of 1.0 μm to 6.5 μm. The positive electrode active material may have a particle size (D90) at 90% of the undersize cumulative particle size distribution in the range of 5.5 μm to 10.0 μm. Furthermore, the ratio D90 / D50 of D90 to D50 of the positive electrode active material may be in the range of 1.3 to 1.9. In this embodiment, the particle size is a value measured by a laser diffraction method.
[0032] The conductive assistant is not particularly limited, and for example, conductive carbon can be used. The shape of the conductive assistant may be, for example, spherical. Carbon black can be used as the spherical conductive carbon. The average particle size of the conductive assistant may be in the range of 0.010 to 0.080 as the ratio of the average particle size of the conductive assistant to the average particle size of the active material (average particle size of spherical carbon / average particle size of the conductive assistant). The average particle size (D50) of the conductive assistant may be in the range of 0.010 μm to 0.50 μm. In addition, the particle size (D90) of the conductive assistant at which the cumulative undersieve particle size distribution is 90% may be in the range of 0.3 μm to 1.0 μm. Furthermore, the ratio D90 / D50 of D90 to D50 of the conductive assistant may be in the range of 0.6 to 100.
[0033] The positive electrode active material layer 22 may further contain a solid electrolyte, a binder, and a dispersant.
[0034] As the solid electrolyte, the same as that used in the solid electrolyte layer 40 can be used. The shape of the solid electrolyte contained in the positive electrode active material layer 22 may be, for example, spherical, polyhedral, or amorphous. The average particle diameter of the solid electrolyte may be in the range of 0.10 to 0.90 as the ratio of the average particle diameter of the solid electrolyte to the average particle diameter of the active material (average particle diameter of the solid electrolyte / average particle diameter of the active material). The average particle diameter (D50) of the solid electrolyte may be in the range of 0.50 μm to 1.5 μm. In addition, the particle diameter (D90) of the solid electrolyte at which the undersize cumulative particle size distribution is 90% may be in the range of 1.5 μm to 3.0 μm. Furthermore, the ratio D90 / D50 of D90 to D50 of the solid electrolyte may be in the range of 1.0 to 4.5. The solid electrolyte contained in the positive electrode active material layer 22 may be partially or entirely coated on the surface of the positive electrode active material.
[0035] The binder is not particularly limited, and may be, for example, a fluororesin or rubber. Examples of the fluororesin include polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE). Examples of the rubber include styrene butadiene rubber (SBR) and ethylene propylene diene rubber (EPDM).
[0036] The dispersant is not particularly limited, and for example, polyvinyl butyral, polyvinylpyrrolidone, and carboxymethyl cellulose can be used.
[0037] The content of each material in the positive electrode active material layer 22 may be, for example, 50% by mass or more and 90% by mass or less of the active material, 10% by mass or more and 50% by mass or less of the conductive assistant, 0% by mass or more and 40% by mass or less of the solid electrolyte, 0% by mass or more and 5% by mass or less of the binder, and 0% by mass or more and 1% by mass or less of the dispersant, with the total amount being 100% by mass. The solid electrolyte content may be 5% by mass or more and 40% by mass or less, the binder content may be 1% by mass or more and 5% by mass or less, and the dispersant content may be 0.05% by mass or more and 1% by mass or less.
[0038] The positive electrode active material layer 22 can be manufactured by applying a slurry for forming a positive electrode active material layer to the surface of the positive electrode current collector 21 and drying it. The slurry for forming a positive electrode active material layer can be manufactured, for example, as follows. First, a binder-containing liquid is prepared. The binder-containing liquid can be obtained by dissolving or dispersing a binder in a solvent. An ester-based solvent can be used as the solvent. An example of an ester-based solvent is butyl butyrate. Next, a conductive assistant and a dispersant are added to the binder-containing liquid and mixed. Next, an active material and a solid electrolyte are added to the binder-containing liquid to which the conductive assistant and dispersant have been added, and mixed. For example, a ball mill can be used for mixing.
[0039] The material of the positive electrode lead wire 23 may be the same as the material of the positive electrode current collector 21, or may be different from the material of the positive electrode current collector 21. The positive electrode lead wire 23 may be integrally connected to the positive electrode current collector 21. The material of the positive electrode terminal 24 may be the same as the material of the positive electrode lead wire 23, or may be different from the material of the positive electrode lead wire 23. The positive electrode terminal 24 may be integrally connected to the positive electrode lead wire 23.
[0040] The material and shape of the negative electrode current collector 31 are not particularly limited as long as it has the function of collecting current from the negative electrode 30. Examples of materials for the negative electrode current collector 31 include nickel, copper, stainless steel, etc. Examples of shapes of the negative electrode current collector 31 include a foil shape, a plate shape, etc.
[0041] The negative electrode active material layer 32 contains at least one type of negative electrode active material. As the negative electrode active material, a material capable of absorbing and releasing lithium ions and a metal that forms an alloy with lithium can be used. As a material capable of absorbing and releasing lithium ions, for example, lithium titanate (Li4Ti5O 12Examples of the metals that can be used include lithium transition metal oxides such as TiO2, Nb2O3, and WO3, metal sulfides, metal nitrides, graphite, and carbon materials such as soft carbon and hard carbon. Examples of the metals that can form an alloy with lithium include Mg, Si, Au, Ag, In, Ge, Sn, Pb, Al, and Zn.
[0042] The shape of the negative electrode active material may be, for example, spherical, polyhedral, or amorphous. The negative electrode active material may have an average particle size (D50) in the range of 1.0 μm to 5.0 μm. The negative electrode active material may have a particle size (D90) at which the undersize cumulative particle size distribution is 90% in the range of 5.5 μm to 7.0 μm. Furthermore, the ratio D90 / D50 of D90 to D50 of the negative electrode active material may be in the range of 1.3 to 1.9.
[0043] The negative electrode active material layer 32 may further contain a conductive assistant, a solid electrolyte, a binder, and a dispersant. The conductive assistant, the solid electrolyte, the binder, and the dispersant may be the same as those exemplified for the positive electrode active material layer 22.
[0044] The material of the negative electrode lead wire 33 may be the same as the material of the negative electrode current collector 31, or may be different from the material of the negative electrode current collector 31. The negative electrode lead wire 33 may be integrally connected to the negative electrode current collector 31. The material of the negative electrode terminal 34 may be the same as the material of the negative electrode lead wire 33, or may be different from the material of the negative electrode lead wire 33. The negative electrode terminal 34 may be integrally connected to the negative electrode lead wire 33.
[0045] The solid electrolyte layer 40 includes at least one solid electrolyte material. Examples of the solid electrolyte material that can be used include a sulfide solid electrolyte material, an oxide solid electrolyte material, a nitride solid electrolyte material, and a halide solid electrolyte material.
[0046] Examples of sulfide solid electrolyte materials include Li2S-P2S5, Li2S-P2S5-LiI, Li6PS5Cl, Li3PS4, etc. The above description of "Li2S-P2S5" means a sulfide solid electrolyte material made using a raw material composition containing Li2S and P2S5, and the same applies to other similar descriptions. The sulfide solid electrolyte material may have an argyrodite-type crystal structure.
[0047] Examples of oxide solid electrolyte materials include NASICON-type oxides, garnet-type oxides, perovskite-type oxides, etc. Examples of NASICON-type oxides include oxides containing Li, Al, Ti, P, and O (e.g., Li 1.5 Al 0.5 Ti 1.5 (PO4)3). Examples of garnet-type oxides include oxides containing Li, La, Zr, and O (e.g., Li7La3Zr2O 12 Examples of perovskite oxides include oxides containing Li, La, Ti, and O (for example, LiLaTiO3).
[0048] The shape of the solid electrolyte contained in the solid electrolyte layer 40 may be, for example, spherical, polyhedral, or amorphous. The average particle size (D50) of the solid electrolyte may be in the range of 3.0 μm to 5.0 μm. The particle size (D90) of the solid electrolyte at 90% of the undersize cumulative particle size distribution may be in the range of 5.0 μm to 10.0 μm. Furthermore, the ratio D90 to D50 of the solid electrolyte, D90 / D50, may be in the range of 1.5 to 3.5.
[0049] The material of the exterior body 50 may be, for example, a laminate film. The laminate film may be a three-layered film having an inner resin layer, a metal layer, and an outer resin layer laminated in this order from the inside. The outer resin layer may be, for example, a polyamide (nylon) layer or a polyethylene terephthalate (PET) layer, the metal layer may be, for example, an aluminum layer, and the inner resin layer may be, for example, a polyethylene layer or a polypropylene layer.
[0050] The secondary battery 1 of this embodiment can be manufactured, for example, as follows. First, the positive electrode 20, the solid electrolyte layer 40, and the negative electrode 30 are laminated in this order, and the resulting laminate is press-bonded to obtain an electrode laminate 10. The electrode laminate 10 may be pressed in the lamination direction to improve the adhesion between the positive electrode 20, the solid electrolyte layer 40, and the negative electrode 30, and to increase the density of the positive electrode active material layer 22 and the negative electrode active material layer 32. Next, a positive electrode terminal 24 is connected to the positive electrode current collector 21 of the electrode laminate 10 via a positive electrode lead wire 23, and a negative electrode terminal 34 is connected to the negative electrode current collector 31 via a negative electrode lead wire 33. Next, the electrode laminate 10 is housed in an exterior body 50, and the exterior body 50 is sealed.
[0051] According to the secondary battery 1 of the present embodiment configured as described above, the average value and standard deviation of the area of the Voronoi region 222 obtained by performing Voronoi analysis on the cross-sectional image of the positive electrode active material layer 22 with the conductive assistant 221 as the generating point are within the above range, and the conductive assistant is uniformly dispersed in the positive electrode active material layer 22, so that the electric conductivity of the positive electrode active material layer 22 becomes uniform. Therefore, ions are easily diffused throughout the positive electrode active material layer 22, and the ion diffusion resistance of the positive electrode active material layer 22 is reduced. Therefore, the operating voltage of the secondary battery 1 at a high current density becomes high.
[0052] In the secondary battery 1 of this embodiment, when the coefficient of variation of the area of the Voronoi region 222 is within the above range, the ion diffusion resistance of the positive electrode active material layer 22 is further reduced, and the operating voltage of the secondary battery 1 at high current density becomes higher. In the secondary battery 1 of this embodiment, when the conductive assistant of the positive electrode active material layer 22 is spherical and the ratio of the average particle diameter of the conductive assistant to the average particle diameter of the positive electrode active material (average particle diameter of the conductive assistant / average particle diameter of the positive electrode active material) is within the above range, the conductive assistant is more easily dispersed uniformly in the positive electrode active material layer 22, and the ion diffusion resistance of the positive electrode active material layer 22 is further reduced. As a result, the operating voltage of the secondary battery 1 at high current density becomes higher. In the secondary battery 1 of this embodiment, when the positive electrode active material layer 22 further contains a solid electrolyte and the ratio of the average particle diameter of the solid electrolyte to the average particle diameter of the positive electrode active material (average particle diameter of the solid electrolyte / average particle diameter of the positive electrode active material) is within the above range, the ion diffusion resistance of the positive electrode active material layer 22 is further reduced. Therefore, the operating voltage of the secondary battery 1 at high current density becomes higher. In the secondary battery 1 of this embodiment, when the average particle diameter of the positive electrode active material is fine within the above range, the surface area of the active material becomes larger, and the ion diffusion resistance of the positive electrode active material layer is further reduced. Therefore, the operating voltage of the secondary battery 1 at high current density becomes higher.
[0053] Although the embodiment of the present invention has been described above, the present invention is not limited to the above embodiment. For example, in the secondary battery 1 of this embodiment, the average value of the area of the Voronoi regions with the conductive assistant of the positive electrode active material layer 22 as the kernel point and the standard deviation of the area of the Voronoi regions are within the above ranges, but the configuration of the electrodes is not limited to this. For example, when the negative electrode active material layer 32 contains a negative electrode active material and a conductive assistant, the average value of the area of the Voronoi regions and the standard deviation of the area of the Voronoi regions obtained by performing a Voronoi analysis with the conductive assistant as the kernel point on an image of a cross section of the negative electrode active material layer 32 may be set to be within the above ranges.
[0054] In the secondary battery 1 of this embodiment, the negative electrode active material layer 32 is disposed on the surface of the negative electrode current collector 31 of the negative electrode 30, and lithium ions are absorbed in the negative electrode active material during charging, and lithium ions are released from the negative electrode active material during discharging, but the configuration of the negative electrode 30 is not limited to this. The negative electrode may be configured such that lithium ions are precipitated on the surface of the negative electrode current collector 31 during charging, and lithium ions are released from the precipitated lithium during discharging, without disposing the negative electrode active material layer 32. In this configuration, lithium foil may be disposed on the surface of the negative electrode current collector 31 to facilitate the precipitation of lithium ions on the surface of the negative electrode current collector 31 during charging.
[0055] Furthermore, although the secondary battery 1 of this embodiment is a solid-state battery, it may be a non-aqueous solvent battery. In the case of a non-aqueous solvent battery, the electrolyte is not particularly limited, and various electrolytes used in non-aqueous solvent batteries can be used. EXAMPLES
[0056] [Example 1] (1) Preparation of coated positive electrode active material As the positive electrode active material, Li(NiCoMn) x O2 (x=0.33) (D50: 3.4 μm, D90: 5.3 μm, D90 / D50: 1.56) was prepared. Li6PS5Cl (D50: 0.6 μm, D90: 1.5 μm, D90 / D50: 2.5) was prepared as a solid electrolyte. The positive electrode active material and the solid electrolyte were mixed in a mass ratio of 90:10 to prepare a coated positive electrode active material in which the surface of the positive electrode active material was coated with the solid electrolyte.
[0057] (2) Preparation of slurry for forming positive electrode active material layer SBR (styrene butadiene rubber) binder was dissolved in butyl butyrate solvent to prepare an SBR binder solution with a concentration of 10% by mass. 2.63 g of the obtained SBR binder solution was weighed out, and 4.31 g of butyl butyrate solvent, 0.79 g of carbon black (spherical carbon, average diameter: 0.1 μm) as a conductive additive, and 0.05 g of PVB (polyvinyl butyral) as a dispersant were added to this SBR binder solution. The obtained mixture was subjected to a first dispersion treatment once by kneading at 2000 rpm for 10 minutes using a rotation-revolution type mixer (Awatori Rentaro ARE310, manufactured by Thinky Corporation).
[0058] 47.6 g of zirconia balls (diameter: 2 mm) and 33.3 g of the coated positive electrode active material obtained in (1) above were added to the mixture after the first dispersion treatment, and then 1.9 g of butyl butyrate solvent was added so that the solid content ratio in the mixture became 80.1 mass %. Thereafter, the mixture was subjected to a second dispersion treatment twice by kneading at 2000 rpm for 1 minute using a rotation-revolution type mixer.
[0059] 3.06 g of the solid electrolyte prepared in (1) above was added to the mixed liquid after the second dispersion treatment, and the positive electrode active material content was adjusted to 80.0 mass%, the solid electrolyte content to 17.1 mass%, the conductive additive content to 2.1 mass%, the binder content to 0.7 mass%, and the dispersant content to 0.1 mass%. Next, 1.4 g of butyl butyrate solvent was added so that the solid content ratio in the mixed liquid was 79.0 mass%. After that, the mixed liquid was subjected to a third dispersion treatment once by kneading at 2000 rpm for 2 minutes using a rotation-revolution type mixer.
[0060] To the mixture after the third dispersion treatment, 4.6 g of butyl butyrate solvent was added so that the solid content ratio in the mixture was 72.0 mass %. Thereafter, the mixture was subjected to a fourth dispersion treatment once by kneading at 2000 rpm for 2 minutes using a rotation-revolution type mixer.
[0061] To the mixture after the fourth dispersion treatment, 0.9 g of butyl butyrate solvent was added so that the solid content ratio in the mixture was 70.8 mass %. Thereafter, the mixture was subjected to a fifth dispersion treatment once by kneading at 2000 rpm for 2 minutes using a rotation-revolution type mixer.
[0062] The mixture after the fifth dispersion treatment was filtered using a sieve with a mesh size of 100 μm to remove the zirconia balls, and the obtained filtrate was used as a slurry for forming a positive electrode active material layer.
[0063] (3) Preparation of the positive electrode An Al current collector was prepared as a positive electrode current collector. The positive electrode active material layer forming slurry obtained in (2) above was applied to the surface of this positive electrode current collector and dried to form a positive electrode active material layer. The obtained positive electrode active material layer was applied to the positive electrode current collector at a rate of 10 ton / cm. 2 The pressure was increased by 100 MPa.
[0064] [Example 2] A positive electrode was prepared in the same manner as in Example 1, except that Li6PS5Cl (D50: 1.0 μm, D90: 3.0 μm, D90 / D50: 3.0) was used as the solid electrolyte in (1) preparing the coated positive electrode active material and (2) preparing the slurry for forming the positive electrode active material layer.
[0065] [Example 3] A positive electrode was prepared in the same manner as in Example 1, except that in (1) preparing the coated positive electrode active material and (2) preparing the slurry for forming the positive electrode active material layer, Li6PS5Cl (D50: 3.0 μm, D90: 8.0 μm, D90 / D50: 2.7) was used as the solid electrolyte, and in (2) preparing the slurry for forming the positive electrode active material layer, the solid electrolyte was added to the mixed solution so that the positive electrode active material content was 60.0 mass%, the solid electrolyte content was 36.0 mass%, the conductive additive content was 2.8 mass%, the binder content was 1.0 mass%, and the dispersant content was 0.2 mass%.
[0066] [Example 4] (2) In preparing the slurry for forming the positive electrode active material layer, a positive electrode was prepared in the same manner as in Example 1, except that a PVdF binder dispersion solution having a concentration of 10 mass % in which a PVDF (polyvinylidene fluoride) binder was dispersed in a butyl butyrate solvent was used instead of the SBR binder solution.
[0067] [Comparative Example 1] A positive electrode was prepared in the same manner as in Example 1, except that Li6PS5Cl (D50: 3.0 μm, D90: 8.0 μm, D90 / D50: 2.7) was used as the solid electrolyte in (1) preparing the coated positive electrode active material and (2) preparing the slurry for forming the positive electrode active material layer.
[0068] [Comparative Example 2] (2) A positive electrode was produced in the same manner as in Example 1, except that in preparing the slurry for forming a positive electrode active material layer, multi-walled carbon nanotubes (fibrous carbon, average diameter in the longitudinal direction: 1.0 μm) were used as the conductive assistant.
[0069] [Comparative Example 3] A positive electrode was prepared in the same manner as in Example 1, except that Li3PS4 (D50: 1.1 μm, D90: 15.0 μm, D90 / D50: 13.6) was used as the solid electrolyte in (1) preparing the coated positive electrode active material and (2) preparing the slurry for forming the positive electrode active material layer.
[0070] (Components of Positive Electrode Active Material Layer) The composition of the positive electrode active material layer of the positive electrode thus obtained and the particle size of each material are shown below.
[0071] [Table 1]
[0072] [evaluation] The Voronoi analysis of the positive electrode active material layers of the positive electrodes obtained in Examples 1 to 4 and Comparative Examples 1 to 3 and the measurement of the diffusion resistance values of the secondary batteries using the positive electrodes were performed by the following method. The results are shown in Table 2 below, together with the ratio of the average particle size of the conductive assistant to the average particle size of the positive electrode active material (D50 of conductive assistant / D50 of positive electrode active material) and the ratio of the average particle size of the solid electrolyte to the average particle size of the positive electrode active material (D50 of solid electrolyte / D50 of positive electrode active material).
[0073] (Voronoi analysis) The positive electrodes obtained in Examples 1 to 4 and Comparative Examples 1 to 3 were cut in the thickness direction. The cut surface of the obtained positive electrode active material layer was observed using a FE-SEM (field emission scanning electron microscope JSM-7001F, manufactured by JEOL Ltd.) with a field area of 1044 μm 2 The observation was performed under the conditions of (length 29 μm × width 36 μm, 3000 magnification). A Voronoi analysis was performed on the backscattered electron image of the positive electrode active material layer, with the conductive additive as the mother point. The average area, standard deviation, and coefficient of variation of the Voronoi region obtained by the Voronoi analysis were calculated. The observation of the cut surface was performed at 30 points, and the average area, standard deviation, and coefficient of variation of the Voronoi region were calculated for each of the 30 points. For the positive electrode active material obtained in Example 1, Fig. 3A shows a secondary electron image of an FE-SEM, and Fig. 3B shows a Voronoi diagram. Figs. 4A to 4G show the frequency distribution of the average area of the Voronoi regions with the conductive assistant as the mother point in one image measured at 30 points on the cross section of the positive electrode active material layer obtained in Examples 1 to 4 and Comparative Examples 1 to 3. Table 2 shows the average area, standard deviation, and average value of the coefficient of variation of the Voronoi regions measured at 30 points.
[0074] (Diffusion resistance value) Weigh out 100 mg of solid electrolyte and apply a pressure of 1.5 ton / cm 2 A molding pressure of 3.0 ton / cm was applied to obtain a solid electrolyte pellet. The positive electrodes obtained in Examples 1 to 4 and Comparative Examples 1 to 3 were placed on one side of the solid electrolyte pellet. 2 Then, it is preformed at 10.0 ton / cm 2 A Li metal plate (1 mm thick) was placed as the negative electrode on the side opposite to the positive electrode side of the solid electrolyte pellet, and the pressure was 1.5 tons / cm.2 A molding pressure of 0.1 C (1 C = 4.0 mA / cm) was applied to the resulting laminate in a laminated state in which the negative electrode, solid electrolyte pellets, and positive electrode were stacked in this order. Terminals were attached to the positive and negative electrodes of the resulting laminate via lead wires, and the laminate was then housed in an exterior body so that the terminals were exposed from the exterior body, and sealed to produce a solid-state battery. The produced solid-state battery was subjected to a test at 0.1 C (1 C = 4.0 mA / cm) under a restraining pressure of 10 MPa and a test environment of 25°C. 2 The solid-state battery was charged and discharged at a current density of 0.1 C, 0.5 C, 1.0 C, 2.0 C, and 3.0 C for 10 seconds. The solid-state battery was then charged again and discharged to 50% of the initial discharge capacity (SOC50%), after which the DC resistance and AC impedance of the solid-state battery were measured. In the DC resistance measurement, the current densities (mA / cm2) when the battery was discharged for 10 seconds at current densities of 0.1 C, 0.5 C, 1.0 C, 2.0 C, and 3.0 C were measured. 2 ) versus potential (V) to create an IV characteristic graph, and the DC resistance was obtained from the slope of the plot of the IV characteristic graph. Figure 5 shows the IV characteristic graph. In the AC impedance measurement, the solid electrolyte resistance and positive electrode reaction resistance (charge transfer resistance) were obtained from an amplitude of 1 Hz-1 MHz at an AC voltage of 10 mV. The diffusion resistance was determined by subtracting the solid electrolyte resistance and positive electrode reaction resistance obtained in the AC impedance measurement from the DC resistance obtained in the DC resistance measurement.
[0075] [Table 2]
[0076] Comparing Figures 4A to 4D with Figures 4E to 4G, it can be seen that the frequency distribution of the average area of the Voronoi regions in the positive electrode active material layers of Examples 1 to 4 is narrower than the frequency distribution of the average area of the Voronoi regions in the positive electrode active material layers of Comparative Examples 1 to 3, and the variation in the average area of the Voronoi regions is smaller.
[0077] From the results in Table 2, it can be seen that the positive electrode active material layers of Examples 1 to 4, in which the average area and standard deviation of the Voronoi regions are within the range of the present invention, have a smaller diffusion resistance value and are easier to diffuse ions, compared to the positive electrode active material layers of Comparative Examples 1 to 3, in which the average area and standard deviation of the Voronoi regions are larger than the range of the present invention. Also, from the IV characteristic graph in FIG. 5, it can be seen that the solid-state batteries fabricated using the positive electrodes obtained in Examples 1 to 4 have a higher operating voltage at high current density, compared to the solid-state batteries fabricated using the positive electrodes obtained in Comparative Examples 1 to 3. This is because the positive electrode active material layers of Examples 1 to 4 are easier for ions to diffuse, and the resistance is less likely to increase even when discharged at a high current density. [Explanation of symbols]
[0078] 1 Secondary battery 10 Electrode laminate 20 positive electrode 21 Positive electrode current collector 22 Cathode active material layer 23 Positive lead wire 24 Positive terminal 30 negative electrode 31 Negative electrode current collector 32 Negative electrode active material layer 33 Negative lead wire 34 Negative terminal 36 Lithium deposit layer 40 Solid electrolyte layer 50 Exterior body 221 Conductive additives 222 Voronoi Region
Claims
1. A current collector and an active material layer disposed on at least one surface of the current collector, The active material layer includes an active material and a conductive assistant, The average area of the Voronoi region obtained by performing Voronoi analysis on the cross-sectional image with the conductive additive as the generating point is 1.00 μm 2 2.50 μm or more 2 An electrode for a secondary battery, wherein the standard deviation of the area of the Voronoi region is 0.20 or less and is within the following range.
2. 2. The electrode for a secondary battery according to claim 1, wherein the coefficient of variation of the area of the Voronoi region is 10.0% or less.
3. The conductive assistant is spherical, 2. The electrode for a secondary battery according to claim 1, wherein a ratio of an average particle diameter of the conductive assistant measured by a laser diffraction method to an average particle diameter of the active material measured by a laser diffraction method is in the range of 0.010 or more and 0.080 or less.
4. Further, the solid electrolyte is included, 2. The electrode for a secondary battery according to claim 1, wherein a ratio of an average particle size of the solid electrolyte measured by a laser diffraction method to an average particle size of the active material measured by a laser diffraction method is within a range of 0.10 or more and 0.90 or less.
5. 2. The electrode for a secondary battery according to claim 1, wherein the average particle size of the active material measured by a laser diffraction method is in the range of 1.0 μm or more and 5.0 μm or less.
6. The electrode for a secondary battery according to claim 1 , which is used for a positive electrode of a secondary battery.
7. A secondary battery comprising the electrode for secondary batteries according to any one of claims 1 to 6.
Citation Information
Patent Citations
Thermoplastic resin film for magnetic record medium
JP1997174678A
Manufacturing method of electrode plate
JP2020140793A
Manufacturing method of cathode active material mixture and inspection method
JP2022121231A
Evaluation method for functional paste and production method for functional paste
JP2022142943A
Silicon nitride substrate evaluation method, silicon nitride substrate evaluation device, silicon nitride substrate evaluation system, silicon nitride substrate manufacturing method, and power module manufacturing method
JP2023050994A